Nonmonotone adaptive trust-region method for unconstrained optimization problems - Fu, Jinhua; Sun, Wenyu (Applied mathematics and computation, 2005)
In this paper, an adaptive trust region method with nonmonotone technique for unconstrained optimization problems is presented and analyzed. The global and local convergence results of the algorithm are established. Numerical results show that the new method is efficient.